ANESTHESIA FOR RENAL TRANSPLANT SURGERY IN ADULTS - Silva, Wallace Andrino; Macêdo Pinheiro, Aline; Correia Junior, Cipriano; Henrique Lima, Paulo; Alves Henrique Costa, Kellen Micheline; Dantas Júnior, José Hipólito; Medeiros, Paulo José (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Renal transplant surgery may be associated with important perioperative complications. In this scenario, the anesthetic technique should provide optimal conditions for the surgical team, guarantee hemodynamic stability and kidney perfusion, and adequate analgesia. Preoperative evaluation should always be performed. In the intraoperative period, standard monitoring is sufficient in most cases. General balanced anesthesia, alone or in combination with spinal anesthesia or peripheral block, is the technique of choice. Management of blood pressure during the surgery is crucial. Before reperfusion, a mean arterial blood pressure of 65 mmHg is recommended, increasing to 80–90 mmHg when reperfusion is imminent until the end of surgery. Vasopressors, such as ephedrine, may be necessary to achieve blood pressure targets. Mannitol and furosemide are commonly used to increase urine output. In the postoperative period, analgesia should be ensured.